BIOCENOSIS OF THE VAGINA IN WOMEN WITH THYROID PATHOLOGY USING VARIOUS METHODS OF CONTRACEPTION - N. K h . Rakhmanova; D.G.Matrizaeva (Scholar Express Journals, 2022)
The target of the research is to study dynamically the state of microbiocenosis of the genital tract in healthy and thyroid women using various contraceptives. Healthy women enable a normal vaginal microbiocenosis than women with thyroid disease. There is a necessity to take into account of negative influence of the different types of contraception on microbiota of genital system of women with thyroid disease in reproductive age.
Keywords: Contraceptives; urogenital system; vaginal microbiocenosis; dysbiosis